2021
DOI: 10.38029/bumj.v4i2.88
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Predictors of Health Service Utilization among Rural and Urban Areas in Ilorin East Local Government Area of Kwara State

Abstract: Objective: Health facilities utilization among Nigerians is affected by access to hospitals and, availability of personnel. This study compared the predictors of health service utilization in rural and urban areas of Ilorin East Local Government Area of Kwara State.                 Method: A cross-sectional study, involving 250 rural and 250 urban respondents selected through multi-stage sampling techniques. Quantitative data were collected using an interviewer-administered questionnaire. Qualitative data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…11,12 Differences in the use of healthcare services between rural and urban areas have been ascribed to many factors, including health service factors in the Nigerian context. [13][14][15] Some of these factors, as cited in several studies, include gender preference and attitude of healthcare workers, lack of male-friendly services, cost of services, distance to health facilities, and long waiting periods at the health facilities. [16][17][18][19][20] Studies conducted in Africa have reported some factors affecting partner involvement in reproductive health services.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Differences in the use of healthcare services between rural and urban areas have been ascribed to many factors, including health service factors in the Nigerian context. [13][14][15] Some of these factors, as cited in several studies, include gender preference and attitude of healthcare workers, lack of male-friendly services, cost of services, distance to health facilities, and long waiting periods at the health facilities. [16][17][18][19][20] Studies conducted in Africa have reported some factors affecting partner involvement in reproductive health services.…”
Section: Introductionmentioning
confidence: 99%